Static performance of a new type of corrugated steel-concrete composite shell under mid-span loading. (March 2022) - Sun, Dawei; Liu, Changyong; Wang, Yuyin; Xia, Qilong; Liu, Faqi
Abstract: This paper proposes a new type of corrugated steel-concrete (CSC) utility tunnel, which is composed of CSC shells. Compared with existing prefabricated concrete utility tunnels, the CSC utility tunnel reduces the requirements for transportation and hoisting and provides additional protection for concrete and rebars from corrosion. The performance of the CSC utility tunnel depends on the behaviors of CSC shells. First, cross-sectional properties were studied by theoretical analyses and it was found that the stiffness can be greatly improved if corrugated steel and concrete work together, reaching 1.43 times that of the simple superposition of corrugated steel and concrete, respectively. To further disclose the fundamental behavior of the CSC shell, six CSC shell specimens with a span of 3 m and different stud intervals (from 100 mm × 100 mm to 400 mm × 400 mm), rise-span ratios (1/10–1/6) and concrete strengths (32.1 MPa and 51.2 MPa) were tested under a static mid-span load. The test results show that all CSC shells failed by strength failure when reached the ultimate load. For specimens with different stud intervals, the strains of the corrugated steel (crest, middle and trough) were measured, and then the composite mechanism between steel and concrete and the confinement effect of corrugated steel to concrete were analyzed. The stud interval has a slight influence on the ultimate bearing capacity in this study, decreasing by 7.5% for the bearing capacity when the stud interval increases from 100 mm × 100 mm to 400 mm × 400 mm. The bearing capacity and the stiffness of the CSC shell decrease obviously with the decreasing of the rise-span ratio. And the bearing capacity improves significantly with the improvement of the concrete strength. Furthermore, a finite element model was developed and was proved to have good accuracy for the prediction of the performance of the CSC shell.